A midsummer night's dream - Shakespeare, William, 1564-1616.; Durband, Alan. (Woodbury, N.Y. : Barron's, 1985)
Presents the original text of Shakespeare's play side by side with a modern version, discusses the author and the theater of his time, and provides quizzes and other study activities.
"Modern version side-by-side with full original text."
Keywords: Courtship -- Drama; Athens (Greece) -- Drama; Shakespeare, William, -- 1564-1616 -- Problems, exercises, etc; Fairy plays; Shakespeare, William, -- 1564-1616.; Plays; Comedies